2005
DOI: 10.1385/mb:29:3:197
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Parameters of Targeted Gene Repair in Mammalian Cells

Abstract: Targeted gene repair uses short DNA oligonucleotides to direct a nucleotide exchange reaction at a designated site in a mammalian chromosome. The widespread use of this technique has been hampered by the inability of workers to achieve robust levels of correction. Here, we present a mammalian cell system in which DLD-1 cells bearing integrated copies of a mutant eGFP gene are repaired by modified single-stranded DNA oligonucleotides. We demonstrate that two independent clonal isolates, which are transcribed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 35 publications
3
65
0
Order By: Relevance
“…Igoucheva et al 31 suggested a model based on the differential accessibility of the DNA strands during transcription to explain the often-observed strand bias in favor of anti-sense ssODNs. 10,11,13,27,30 During transcription, ssDNA regions are provided that facilitates annealing of complementary ssODN. The increased accessibility of the non-transcribed strand could promote annealing of anti-sense ssODNs, whereas the RNA polymerase activity on the transcribed strand could lead to displacement of sense ssODNs.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Igoucheva et al 31 suggested a model based on the differential accessibility of the DNA strands during transcription to explain the often-observed strand bias in favor of anti-sense ssODNs. 10,11,13,27,30 During transcription, ssDNA regions are provided that facilitates annealing of complementary ssODN. The increased accessibility of the non-transcribed strand could promote annealing of anti-sense ssODNs, whereas the RNA polymerase activity on the transcribed strand could lead to displacement of sense ssODNs.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
“…8,9 Unfortunately, targeting frequencies in mouse ESCs range from 10 À7 to 10 À4 , which is relatively low compared with those found in other cell types. [10][11][12][13][14] A better understanding of the reaction parameters governing ssODN-mediated gene targeting in ESCs 15,16 is imperative to improve the applicability of the technique. Although different DNA repair pathways may impinge on the targeting process, we will particularly address the role of the DNA mismatch repair (MMR) system that imposes a strong barrier to effective application of ssODN-mediated gene targeting.…”
Section: Introductionmentioning
confidence: 99%
“…22 Transition to single strands was prompted initially by in vitro studies on mechanism carried out by Gamper et al, and by results in mammalian cell culture (see Liu et al 2 and references therein). Important proof-of-concept experiments have been conducted in model systems where the repair of mutations in eGFP, 8,23,24 LacZ, 25,26 HPRT, 27,28 and retinoblastoma genes, 21 albeit at different frequencies, is effectively directed by a single-stranded vector. Partially duplexed oligonucleotides containing regions of singlestranded character have also been shown to be effective, but do not appear to be as active as the completely single-stranded molecule.…”
Section: Single-stranded Dna Catalyzes Gene Repair Most Effectivelymentioning
confidence: 99%
“…This model would also predict that cells in S phase are more amenable to gene repair activity and recent data strongly suggest that this is the case. 24,36,42,48 Correction-yes, but at what price?…”
Section: The Dna Replication Process Regulates Gene Repair Activitymentioning
confidence: 99%
“…Additionally, the strand bias was not due to replication (lagging versus leading strand syntheses), since the target plasmids lack a mammalian origin of replication. It has been shown that the strand bias of gene correction by a ss oligonucleotide in mammalian cells was affected by various factors (18)(19)(20)(21). It will be important to determine the actual reason(s) for the strand bias of gene correction by the longer ss DNA fragments used in this study.…”
Section: Discussionmentioning
confidence: 99%